Sistem Informasi Jadwal Pemeliharaan Dan Perbaikan Perangkat Komputer Berbasis Online Di Laboratorium SMP Negeri 20 Surakarta - Yuwanto, Wahyu; Pantjarani, Ari; Naury, Chairullah (Indonesian Journal of Information Technology and Computing (IMAGING), 2024)
The SMK N 20 Surakarta Laboratory currently needs an application program for an online scheduling system to make the work of laboratory technician staff easier. Management of current maintenance and repair schedule data still uses manual recording. Manual recording has the weakness of being easily damaged due to exposure to water and tearing. In addition, the double recording model from the general ledger to Microsoft Excel takes a lot of time, causing delays in maintenance and repair schedules for computer equipment. Based on these problems, the researcher proposes to design an online-based maintenance and repair schedule information system at SMP N 20 Surakarta through this research. The aim of this research is to design a scheduling information system that is real time and can be accessed from anywhere. Researchers used the SDLC (System Development Life Cycle) method in the process of developing a maintenance and repair schedule information system. The programming language used is PHP and MySQL database. With the existence of an online-based maintenance and repair schedule information system, it is hoped that maintenance of computer equipment in the SMP N 20 laboratory will not be hampered.